Mantas poliméricas multicamadas com gradiente de molhabilidade produzidas via fiação por sopro em solução - Sorigotti, Amanda Rinaldi (Universidade Federal de São Carlos, 2023)
The skin is the organ with the most considerable body extension, performing several vital functions. However, due to contact with the external environment, this organ is more susceptible to injuries. As a fundamental part of the treatment of these, there are wound dressings, whose functionalities and efficiency depend on the surface properties of the materials that compose them, especially topography and wettability. In this study, multilayer mats with a wettability gradient 3 from hydrophilic to (ultra/super)hydrophobic 3 were developed, consisting of nanofibers based mainly on cellulose acetate (CA) processed via solution blow spinning (SB-Spinning). For this, solutions with different CA concentrations were prepared together with poly(ethylene oxide) (PEO) and poly(ethylene glycol) (PEG), the latter being used to modulate the wettability of nanofibers, aiming to make them hydrophilic. As a solvent for the mentioned polymers, a mixture of formic and acetic acids (2:1 v/v) was used, with the occasional addition of dichloromethane (DCM). Initially, the CA spinning conditions were optimized, showing that adding 0.24% m/v of PEO was fundamental for obtaining nanofibers. After understanding the isolated effects of the spinning variables and optimizing them for the layers with different wettability 3 hydrophilic, hydrophobic, and ultrahydrophobic 3, the multilayer mats were produced from the optimized conditions selected. As a result, there was an interaction between the layers, contributing to their water absorption capacity and water vapor transmission rate suitable for skin wound dressings. Furthermore, there was no growth of S. aureus and P. aeruginosa bacteria on both sides of the mat up to 48 h. Therefore, it is concluded that the multilayer mats are promising materials for the intended application because they mimic the skin's structure and act in the healing process, reducing the incidence of bacterial infections.
Multilayer polymer mats with wettability gradient produced via solution blow spinning
Keywords: Biomateriais; Acetato de celulose; Gradiente de molhabilidade; Hidrofobicidade; Fiação por sopro; Curativos; Bactérias; Biomaterials; Cellulose acetate; Wettability gradient; Hydrophobicity; Blow spinning; Wound dressings; Bacteria; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA